ACCENT, RHYTHM, MELODY AND TIMBRE (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
This article explores the role of accent, rhythm, melody, tempo, and timbre in the fields of lexicology and linguistics, emphasizing their importance in shaping meaning, emotional tone, and communicative effectiveness. It delves into the definitions and functions of each element, explaining how they contribute to the structure and interpretation of language. The discussion highlights how these auditory features work independently and in concert to influence spoken communication, affect listener perception, and add richness to linguistic expression.